Survey of the impacts of soil and climatic variations on the production of essential oils in Heracleum persicum - RAHELE HASANI; IRAJ MEHREGAN; KAMBIZ LARIJANI; TAHER NEJADSATTARI; ROMAIN SCALONE (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Hasani R, Mehregan I, Larijani K, Nejadsattari T, Scalone R.2017. Survey of the impacts of soil and climatic variations on the production of essential oils in Heracleum persicum Biodiversitas 18: 365-377.Essential oils have been extracted from different parts of the Heracleum persicum plants (Apiaceae) since many years. However, the effect of the climate and the soil composition on their quality and quantity of the essential oils have never been investigated in this species. For this aim, ten populations of Persian hogweed were selected regarding their different localities in Iran and their essential oils were extracted from dry fruits by hydrodistilation clevenger type, GC-FID and GC-MS analyses. During the sampling of the Heracleum populations, certain climatic and edaphic parameters were also recorded. Within these ten populations, 18 to 43 different oil compounds were identified expanding the diversity of chemical compounds found in Iranian populations. Certain rare molecules as per example the isopropyl-2-methyl butyrate, the isopropyl-3-methyl butyrate, the Î³-terpinene or the p-cymene should be considered to categorize the different populations between them within the species. Certain environmental factors (e.g., EC, Cl, P) are related with the production of certain essential oils within the studied populations and are providing crucial information for the production of these oils by this aromatic herb. To conclude, the study of the environment of the populations can help to improve the utility of this aromatic plant, although certain preliminary results have still to be confirmed by controlled-environment experiments. Keywords: Apiaceae, chemotaxonomy, ecological factors, Persian hogweed